1995
DOI: 10.1142/s0192415x95000031
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Cerebral Cortex in Acupuncture Modulation of the Somesthetic Afferent

Abstract: It is known from previous work that acupuncture stimulation modifies the somesthetic afferent to different extends depending on the acupoint studied. In this study, somatosensory evoked potentials of 21 healthy volunteers are recorded. When acupoint LI-4 (Hoku) is stimulated, it produces noticeable modifications, with a significant increase of latency and decrease of amplitude of the peaks which reflect the primary cortical afferent. Comparison of these results with the absence of changes when the experiment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…After electro puncture of the APs lying in the meridians, obvious antinociceptive effects arose (22). Considerable changes in nociceptive evoked potentials were observed in human brains after AP GI-4 stimulation, but such changes did not appear if the adjacent nonacupuncture area was stimulated (33). Introduction of the acupuncture needle into the human AP E-36 produced specific changes in the spectrum of the radial arterial pulse, but such changes did not occur if the needle was introduced into the skin outside the AP (34).…”
Section: The Effect Of P Light On Formalin-induced Pain Behaviourmentioning
confidence: 99%
“…After electro puncture of the APs lying in the meridians, obvious antinociceptive effects arose (22). Considerable changes in nociceptive evoked potentials were observed in human brains after AP GI-4 stimulation, but such changes did not appear if the adjacent nonacupuncture area was stimulated (33). Introduction of the acupuncture needle into the human AP E-36 produced specific changes in the spectrum of the radial arterial pulse, but such changes did not occur if the needle was introduced into the skin outside the AP (34).…”
Section: The Effect Of P Light On Formalin-induced Pain Behaviourmentioning
confidence: 99%
“…The action of both metameric (Abad-Alegría and Bono, 1988;Melendo and Abad-Alegría, 1991;Abad-Alegría and Bono, 1992) and central (Abad-Alegría and Galve, 1993;Abad-Alegría et al, 1995a and1996) acupunctural stimulus has been demonstrated by neurophysiological methods, which are corroborated by the few external studies published on the same subjects (Yamauchi et al, 1976;Hsieh, 1998;Wei et al, 2000;Bossi et al, 1984;Knardhal et al, 1998). The purpose of this research, carried out in the field of simple somesthesia, is to find out whether De-Qi has any objective neurological correlate.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have shown that acupuncture could modify somatosensory evoked potentials (SEPs) to conventional stimuli 13 and pain stimuli, 4,5 less study has been done on the SEPs elicited by acupuncture itself. In addition, the stimulating method of those few studies on SEPs elicited by acupoint stimuli had been carried out with surface electrodes, 6,7 but the clinical practice of acupuncture is mostly performed by inserting the needle inside the body.…”
Section: Introductionmentioning
confidence: 99%